Nitrobenzene as a Buffer Gas Modifier in Ion Mobility Spectrometry: Better Separations and Cleaner Spectra - Fernandez-Maestre, Roberto; Wu, Ching; H. Hill, Herbert (Current Analytical Chemistry, 2013)
New separations methods are required that meet requirements of contemporary technology such as low cost, speed, and portability of instruments. Ion mobility spectrometry (IMS) complies with these requirements. In this work, IMS was modified by introducing nitrobenzene (NB) into the buffer gas of a mobility spectrometer to differentially increase the drift times of test compounds. Ion mobilities of tetramethylammonium (TMA), tetraethylammonium (TEA), tetrapropylammonium (TPA), and tetrabutylammonium (TBA) ions, 2,4-dimethyl pyridine (2,4-lutidine), 2,6-di-tert-butyl pyridine (DTBP), ethanolamine, atenolol, and valinol decreased depending on their structures. We used an ion mobility spectrometer with electrospray ionization coupled to a quadrupole mass spectrometry. The drift times of the analytes increased according to the amount of NB introduced into the buffer gas and analyte structure. When the amount of NB increased from 0.0 to 1.0 mmol m-3, percent increases in drift times were: ∼ 80% (water clusters), 62% (ethanolamine), 24% (valinol), 15% (2,4-lutidine), 2.6% (arginine), 2.1% (atenolol), 0.9% (TMA), 0.4% (TPA), and 0.2% (DTBP, TEA, and TBA). These differences in drift time change were due to formation of large analyte ion-NB clusters. The small change in mobility of tetraalkylammonium ions and DTBP with the introduction of NB into the buffer gas was explained by steric hindrance of bulky substituents which shielded the positive charge of the ion from the attachment of NB molecules, and delocalized the positive charge. NB in the buffer gas produced ion clusters with one or two NB molecules in compounds with little steric hindrance such as ethanolamine.
Keywords: mass spectrometry